2010
DOI: 10.1037/a0017768
|View full text |Cite
|
Sign up to set email alerts
|

SOCIAL: An integrative framework for the development of social skills.

Abstract: Despite significant advances in the field of social neuroscience, much remains to be understood regarding the development and maintenance of social skills across the life span. Few comprehensive models exist that integrate multidisciplinary perspectives and explain the multitude of factors that influence the emergence and expression of social skills. Here, a developmental biopsychosocial model (SOCIAL) is offered that incorporates the biological underpinnings and socio-cognitive skills that underlie social fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
466
2
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 504 publications
(512 citation statements)
references
References 422 publications
(471 reference statements)
23
466
2
21
Order By: Relevance
“…In a neuropsychological assessment, executive functions are a translation of a broad variety of cognitive functions such as attention, concentration, stimulus selection, abstract thinking, planning, cognitive flexibility, self-control and operational memory. 29 An adequate social functioning depends on the integrity of executive functions, 30 and a decline in executive functions has early association with functional dependence. 31 The exchange of online messages, therefore, demands an adequate social and executive functioning.…”
Section: ) (Continuation) Tabela 4 -Razões De Prevalência (Rp) Brmentioning
confidence: 99%
“…In a neuropsychological assessment, executive functions are a translation of a broad variety of cognitive functions such as attention, concentration, stimulus selection, abstract thinking, planning, cognitive flexibility, self-control and operational memory. 29 An adequate social functioning depends on the integrity of executive functions, 30 and a decline in executive functions has early association with functional dependence. 31 The exchange of online messages, therefore, demands an adequate social and executive functioning.…”
Section: ) (Continuation) Tabela 4 -Razões De Prevalência (Rp) Brmentioning
confidence: 99%
“…For instance, survivors of childhood TBI with inhibition deficits demonstrate difficulties regulating appropriate behavioral responses (Beauchamp & Anderson, 2010). At present, childhood TBI research has demonstrated the persistence of EF deficits up to 10 years post injury (Faber et al, 2016;Muscara et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in these domains have been associated with difficulties in everyday functioning, such as regulating socially appropriate emotional and behavioral responses (Beauchamp & Anderson, 2010;Ganesalingam, Yeates, Sanson, & Anderson, 2007;Gioia, Isquith, Guy, & Kenworthy, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once social skills are influenced by personal, situational and cultural factors there are, in the literature, various definitions and forms of implementation thereof (Beauchamp & Anderson, 2010).…”
Section: Social Skills Self-efficacy Beliefs and The Perception Of Smentioning
confidence: 99%